Pharmacist health coaching in Australian community pharmacies: What do pharmacy professionals think?. (5th February 2020) - Singh, Harjit K.; Kennedy, Gerard A.; Stupans, Ieva
Abstract: Health coaching is a service provided to patients by healthcare professionals for the purposes of disease management and health risk prevention. Internationally, pharmacist health coaching services provided to patients with chronic health conditions have produced beneficial health outcomes. Despite this, the service is not currently provided within Australian community pharmacies. This study evaluates the knowledge, opinions and attitudes of leaders within the pharmacy profession about the concept of health coaching as a service in community pharmacy. Semi‐structured interviews with leaders in the pharmacy profession were carried out. Pharmacy leaders were interviewed until data saturation was reached; 10 pharmacists were interviewed. The interviews were transcribed verbatim and analysed thematically; extracts from the transcripts were compared and categorised to establish themes and subcategories. Analysis of the transcripts indicated the emergence of two main themes and 10 subcategories. The main themes were as follows: 'positive view of health coaching in Australian community pharmacy' and 'barriers to integrating health coaching into Australian community pharmacy'. There was an overall perception that health coaching within community pharmacies would be valued by the Australian community. Interviewees held differing perceptions of pharmacists' capability to effectively coach pharmacy clients and suggested that the main impediments to its introduction related to remuneration for the service. The findings indicated that there is a potential for pharmacists to provide a health coaching service in community pharmacies, but that remuneration is a fundamental barrier. The research also indicated the need to clearly identify the knowledge, skills and attitudes needed to health coach and to identify whether potential gaps in the competencies of Australian community pharmacists exist.